(untitled) (Journal of Information Technologies in Education (ITE), 2012)
One of the promising directions of improving the quality of training future professionals in the Bologna process is the implementation of informative-communicative technologies (ICT) in the educational process of higher education. The article opens the question of the use of informative-communicative technologies in process of formation of the selfeducational competence in teachers of primary school.